The role of digital trust as a moderating variable between digital financial literacy and the use of fintech by small and medium enterprise actors - Nella Ica Devinta; Ario Putrdianto (Universitas Nusa Cendana, 2026)
This study examines the implementation of intellectual enhancement in personality development through a literacy corner program at the Class IIA Correctional Institution in Tangerang. The program is part of the broader correctional development system (SPPN), aiming to improve inmates’ literacy skills and support their personal growth. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis. The study is guided by literacy theory and the concept of correctional development (SPPN). The findings indicate that the literacy corner and library program are relatively effective in enhancing inmates’ intellectual capacity. Inmates actively use the library to gain knowledge, engage in positive activities during their free time, and improve their reading and comprehension skills. The program includes activities such as reading, writing book summaries, and participating in group discussions, which contribute to both cognitive and personal development. However, several challenges remain. Not all inmates participate actively in the program, the availability of reading materials is still limited in certain areas, and there is a lack of dedicated literacy mentors to guide and support inmates consistently. In conclusion, the literacy-based development program has a positive impact on inmates’ intellectual growth, but its effectiveness can be further enhanced by increasing participation, expanding library resources, and providing more structured mentoring support. Keywords: Digital Financial Literacy; Digital Trust; Fintech Utilisation; MSMEs